High-density substrate mapping of the left ventricle as a guide for endomyocardial biopsy: an omnipolar, bipolar, and cardiac magnetic resonance imaging perspective. (19th May 2022) - Casella, M; Compagnucci, P; Volpato, G; La Piscopia, V; Bondavalli, B; Valeri, Y; Cipolletta, L; Parisi, Q; Molini, S; Misiani, A; Messano, L; Ricciotti, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The recent introduction of Omnipolar Technology (OT) has the potential to improve ventricular substrate characterization. In fact, the amplitude of omnipolar electrograms is less dependent of the propagation direction of the recorded wavefront than that of bipolar electrograms, potentially increasing the sensitivity for the detection of viable myocardium by electroanatomical voltage mapping (EVM). Purpose: To assess the presence and extension of dense scar regions and low-voltage areas in omnipolar voltage (OV) maps of the left ventricle (LV) as compared to standard bipolar endocardial maps and cardiac magnetic resonance (CMR)-derived pixel signal intensity (PSI) maps, among patients undergoing EVM-guided endomyocardial biopsy (EMB). Methods: The study included 10 patients undergoing LV substrate mapping and EVM-guided EMB at our institution using the Advisor HD Grid mapping catheter. Before the procedure, contrast enhanced-CMR was obtained for each patient and PSI maps were derived from late gadolinium enhancement sequences with the ADAS-VT software. Scar core and border zone areas were measured in PSI endocardial (10-40% of wall thickness) maps and compared to dense scar regions (<0.5 mV) and low-voltage areas (0.5-1.5 mV) measured by standard bipolar endocardial mapping and OV endocardial mapping, respectively. Continuous variables were checked for normality with the Shapiro-Wilk test, and are reported as mean±standard deviation or median [1st-3rd quartile], as appropriate. Statistical comparisons among the three types of mapping (PSI mapping, standard bipolar, and OV) were performed with Friedman test with post-hoc sign test, as appropriate. P values<0.05 were considered statistically significant, and all analyses were performed with the software RStudio. Results: The indication for EVM-guided EMB was a clinical suspicion of arrhythmogenic or inflammatory cardiomyopathy in all cases. Dense scar regions and low voltage areas detected by OV (dense scar: 2.2 [1.2-6.9] cm2; low voltage areas: 8±3.8 cm2) and standard bipolar mapping (dense scar: 3.4 [2.3-9.6] cm2; low voltage areas: 8.4±4 cm2) were similar to scar core and border zone areas shown by PSI maps (scar core: 1.6[0.6-2.9] cm2; border zone: 3.9[3.7-7.6] cm2; all p=NS). However, dense scar regions were less widespread with OV mapping that with standard bipolar mapping (Friedman test p=0.07; adjusted p=0.006, Figure). The diagnostic yield of EMB measured 80%, whereas mean procedural and fluoroscopy times were 136±30 min and 11±4 min, respectively. Conclusion: OV mapping allowed a refinement of endocardial substrate maps of the LV as compared to standard bipolar mapping, by reducing the dependency of electrogram amplitude on the direction of propagation, thus allowing the detection of viable myocardium even in bipolar scar regions. Therefore, OV mapping may soon become a preferred approach for EVM-guided EMB.